KARAKTERISASI DAN POTENSI KATALIS KARBON AKTIF TERSULFONASI LIMBAH KAYU PADA REAKSI HIDROLISIS SEKAM PADI MENGGUNAKAN MICROWAVE - Lisna Efiyanti; Sutanto; Dian Anggraini Indrawan; Gustan Pari (Jurnal Penelitian Hasil Hutan, 2019)
Lignocellulose biomass is a raw material for developing various promising products, such as wood waste, which can be used as raw material for the production of activated carbon as a catalyst. This research aims to characterize activated carbon for hydrolisis catalyst. In this study, the process of making activated carbon from mixed camphor and meranti wood was made through pyrolysis process at temperature of 500°C, followed by sulfonation using H2SO410N on reflux. The sulfonated activated carbon product (KA-SO3H) was then characterized according to Indonesia National Standard (SNI) including recovery value, moisture content, ash content, fly ash, fixed carbon, iodine absorption, while acidity and functional groups were measured using amonia adsorption and FTIR analysis, respectively. Furthermore, the sulfonated activated carbon was tested for its application in the hydrolysis reaction of rice husks using microwave with vary rice husk weight namely 2, 4 ,6 ,8, and 10 g at 400 and 600 W for 5, 7, and 9 minutes, respectively. The filtrate was then analyzed for its glucose levels using the DNS method (Dinitrosalycilic acid). The optimum condition of the hydrolysis reaction using sulfonated activated carbon catalyst were 400 W power, 1:8 ratio of rice husk and catalyst in 9 minutes duration. The optimum condition produced 330.51 ppm glucose levels with glucose yield percentages was 61.97%, and required energy was 216 kJ.